Strip tillage and crop residue retention decrease the size but increase the diversity of the weed seed bank under intensive rice-based crop rotations in Bangladesh - Hossain, Mohammad Mobarak; Begum, Mahfuza; Hashem, Abul; Rahman, Md. Moshiur; Ahmed, Sharif; Hassan, Montaser M.; Javed, Talha; Shabbir, Rubab; Hadifa, Adel; EL Sabagh, Ayman; Bell, Richard W. (MDPI, 2021)
Cropping under conservation agriculture (CA) has become increasingly attractive among farmers in recent years. However, weed control may be more difficult during the transition to CA from conventional establishment methods due to the reduction in tillage intensity. Conversely, CA changes to weed dynamics can alter the weed seed bank in the longer run. In Bangladesh’s intensively cropped rice-based rotations, the nature of weed seed bank shifts over time after adopting CA are poorly known. Two 2-year studies were sampled from on-farm CA experiments under wheat-mungbean-winter rice and monsoon rice-mustard-winter rice rotations. We investigated the effects of reduced soil disruption in the form of strip-tillage (ST) combined with increased deposition of standing reside from previous crops (0 vs. 50%). The weed seed bank in 0–5, 5–10, and 10–15 cm depths of soil were quantified in a shade-house experiment by measuring weed emergence over 12 months in seedling trays. After 2 years of field study, the year-round count of emerged weeds from the seed bank showed that ST plus 50% mulch had a lower weed abundance and biomass and fewer weed species than that of conventional tillage (CT) without residue. The perennial weeds Ageratum conyzoides L., Alternanthera philoxeroides L., Cynodon dactylon L., Cyperus rotundus L., Jussia decurrence Walt., Leersia hexandra L., Scirpus mucronatus (L.) Palla., and Solanum torvum Sw. were enriched in the smaller-sized ST seed banks in terms of both density and biomass. The CT, on the other hand, was dominated by annual weeds: Cyperus difformis L., Cyanotis axillaris Roem., Echinochloa crus-galli (L.) Beauv., Eleusine indica L., Fimbristylis miliacea (L.) Vahl., and Rotala ramosior L. Overall, ST plus 50% residue had a more diverse seed bank than CT without mulch. The majority of weed seeds were amassed in the 0–5 cm soil depth of the ST, while most of them were accumulated in the 10–15 cm layer of the CT. The wheat-mungbean-winter rice rotation had a more diverse floristic composition with many more weed species than the monsoon rice-mustard-winter rice rotation.